Bioaccumulation of Trace Metals for Daily Fish Consumption from Selected Former Tin Mining Ponds in Peninsular Malaysia: A Review on Safety of Fish Consumption - Rosli, Mohd Hafiz; Md Joni, Amirul Azuan; Malik, Nur Khaliesah Abdul (Makara Journal of Science, 2021)
Tin mining was the predominate mining industry in Malaysia, especially during the mid-19th century. Most of the former mining areas have been reused for aquaculture purposes. Fish produced from former mining areas have been misunderstood as a high health risk if consumed due to their likelihood of containing high heavy metal content in their tissue. Therefore, we review national information on trace metals levels in the tissue of fish from selected former mining ponds in Peninsular Malaysia, together with background concentration of trace metals in their surroundings and food security and human health implications. Seven trace metals (Cu, Zn, As, Cd, Pb, Cr, and Ni) were observed in the water column and sediment. Various reports showed that background trace metal concentrations in the former mining area are mostly lower than several established limits (which were used as the main reference), except for the areas that were being treated for secondary use. Trace metal concentrations in the fish tissue also showed the same trend of high concentrations due to improper or unfinished treatment of former mining ponds. In the context of food safety, various local reports have shown that the consumption of aquaculture products from former mining areas over a lifetime is unlikely to cause any harmful effects and hence may be regarded to be safe. However, these findings are restricted due to the limited studies in Peninsular Malaysia. Therefore, extensive study regarding this particular issue is highly recommended